Instructional Assessment of Technology and Livelihood Education (TLE) Program - Vangilit G. Retome; Nonita C. Estrella; Avelina Sarvida; Imelda Yaoyao; Gary C. Garcia; Dominador Granada (Philippine Association of Institutions for Research, Inc., 2012)
The study was conducted to assess the TLE program instruction of Southern Leyte State University-San Juan campus. It tried to evaluate the attitude of TLE teachers towards work, students personal view about the course, and the physical and learning environment of the school in relation to TLE program. It utilized descriptive survey using two types of self-made questionnaire, the Linkerts Scale and the Open-ended type survey. The data gathered were treated using weighted mean and the frequency count. Results showed that most of the teachers who are teaching TLE are in retiring age (7 out of 11 or 64%). The attitudes of TLE teachers toward the program are moderately positive while the students' personal view towards the course is moderately low. Both teachers and students believed that the school needs to update instructional materials, tools, and equipments, and improve classrooms particularly home technology building. With these findings, the researchers came up with recommendations which are to revisit the TLE curriculum in order to ensure relevance of the program to the present career pathways in Technology and Livelihood Education Program of the Department of Education for secondary schools to hire new teachers specializing TLE and to conduct proper orientation of first year students about the TLE program.